PERGESERAN PARADIGMA PENDIDIKAN DI INDONESIA - ahmad zainuri (Conciencia, 2016)
Immensity and depth insights will give the color and meaning of its own, in doing the steps the construction of "capacity building" education and positioning it to be urgent. For example, like in the context of raising the teachers’ competency of. Poverty of the insight looked at a change of education paradigm; strengthen the notion that it was one of the causing factors that was resulting in reduced the quality of education in Indonesia because education agents were not able to bring it to the proper education that was in accordance with the development and the demands of the times. The Insights of education paradigm was to be something that was urgent to be understood by educators because it can give a thought to affect in running the duties and functions. Be Innovative of understanding about changes of education paradigms and to be able to determine the other education paradigm in line with the progress of science, because the paradigm that appeared because of the progress of knowledge, either because of pure or applications. Education paradigm of Indonesia first in the homeland was a public school paradigm, shift to the paradigm of the state schools, shift to the paradigm of community schools. The paradigm of community schools as a new paradigm was what will be discussed in this paper.